How Donor and Surgical Factors Affect the Viability and Functionality of Human Hepatocytes Isolated From Liver Resections - Solanas, Estela; Sanchez-Fuentes, Nieves; Serrablo, Alejandro; Lue, Alberto; Lorente, Sara; Cortés, Luis; Lanas, Angel; Baptista, Pedro M.; Serrano, M. Trinidad (Frontiers in Medicine, 2022)
Liver resections are a significant source of primary human hepatocytes used mainly in artificial liver devices and pharmacological and biomedical studies. However, it is not well known how patient-donor and surgery-dependent factors influence isolated hepatocytes’ yield, viability, and function. Hence, we aimed to analyze the impact of all these elements on the outcome of human hepatocyte isolation. Patients and methods: Hepatocytes were isolated from liver tissue from patients undergoing partial hepatectomy using a two-step collagenase method. Hepatocyte viability, cell yield, adhesion, and functionality were measured. In addition, clinical and analytical patient variables were collected and the use or absence of vascular clamping and its type (continuous or intermittent) plus the ischemia times during surgery. Results: Malignant disease, previous chemotherapy, and male gender were associated with lower hepatocyte viability and isolation cell yields. The previous increase in transaminases was also associated with lower yields on isolation and lower albumin production. Furthermore, ischemia secondary to vascular clamping during surgery was inversely correlated with the isolated hepatocyte viability. An ischemia time higher than 15 minutes was related to adverse effects on viability. Conclusion: Several factors correlated with the patient and the surgery directly influence the success of human hepatocyte isolation from patients undergoing liver resection.